The cyclical behavior of the term structure of interest rates - Kessel, Reuben A.; National Bureau of Economic Research (New York : National Bureau of Economic Research distributed [by] Columbia University Press, London, 1965)
In this volume, the term structure of interest rate (the relationship between yields or internal rates of return and maturities of default-free securities, is analysed by three independents theories.
Includes bibliographical footnotes.
lje 25/01/2019
Loans
Keywords: Interest rates; Economic policy; Economic development